PARAMETRIC STUDY OF DETERMINATION OF HORIZONTAL SEISMIC COEFFICIENT REDUCTION IN PORT RETAINING WALLS NUMERICALLY USING DYNAMIC ANALYSIS APPROACH - Edbert, Ivan
Dynamic analysis in analyzing the seismic conditions of a retaining wall is quite complicated to perform, so pseudo-static analysis is commonly performed. The pseudo-static analysis uses 100% of the PGAM value. However, based on the results of studies that conducted centrifuge testing and numerical studies on a retaining wall model, it was found that the pseudo-static analysis overestimated the earthquake force. Furthermore, there has been no research using a retaining wall model in the port. So, a coefficient is needed to reduce the results of pseudo-static analysis on retaining walls in port. This study aims to determine the horizontal seismic coefficient reduction factor of retaining walls in port by varying several parameters in the modeling, namely soil site class (SE and SD), earthquake source (subduction and shallow crustal), free standing height of retaining walls (10 m, 15 m, and 20 m), and peak bedrock acceleration (0.1 g, 0.3 g, and 0.5 g). In addition, this study also aims to establish the relationship between the varied parameters and the horizontal seismic coefficient reduction factor of the retaining wall. The analysis in this study was carried out numerically using a dynamic analysis approach. The results of the dynamic analysis were compared with the pseudo-static analysis using the Mononobe-Okabe method. Then, a factor multiplied by the horizontal seismic coefficient was iterated to reduce the value of the coefficient until the resulting seismic lateral earth pressure in the pseudo-static analysis was similar to that in the dynamic analysis. The results show that the horizontal seismic coefficient reduction factor of the retaining wall in the port ranges from 0.2 - 0.63. Then, the flexibility of the soil and retaining wall is inversely proportional to the horizontal seismic coefficient reduction factor, while the earthquake load is directly proportional.